The relationship between inflation, exchange rate and stock prices toward GDP in Malaysia - Boon, Siaw Khim (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The purpose of this study is to investigate the relationship between inflation, exchange rate and stock prices toward GOP in Malaysia as less similar studies were found. Through this study, the existence of bidirectional relationships of inflation, exchange rate and stock prices to GOP were detennined as the interaction between these variables are importance as indicator for the health of economy in MalaYSia.) This study was carried out using quarterly time series data from period of 2000 to 2011 in where GOP as dependent variable while inflation (CPI), exchange rate (NEER) and stock prices (SP) as independent variables. The empirical analysis choose were Unit Root test, Johansen Cointegration test, Granger Causality test and Vector Error Correction Model. The result for inflation and exchange rate to GOP was not significant as well as GOP does not Granger cause inflation, exchange rate and stock prices. While for stock prices, there is unidirectional result from stock prices to GOP. This means the economic growth is affected by the fluctuation of stock prices whereas the stock prices are not suggested to predict the growth of GOP. In conclusion, the stock price is a good economic indicator to be emphasized by the Government financial policy to stabilize the economic growth.